Assessing the revised clinical institute withdrawal for alcohol scale (CIWA-Ar) use at Stikland Hospital - Muddapah, Creeshen Pillay (Stellenbosch : Stellenbosch University, 2022)
Thesis (MMed)--Stellenbosch University, 2022.